Processing and systemazation of bibliographic material in information units – Usme - Valbuena Quiñonez, Martha Cecilia
SENA, the National Learning Service aims to “participate in technological, occupational and social research anddevelopment activities that contribute to updating and improving a comprehensive professional training”. Forthis reason, it adopts the commitment to community libraries, which are located in places with little accessibilityto information. Based on the above, the processes developed in La Huerta community library are promoted, withCajón Viajero being its key drawing for animation and promotion of reading through the users who participatein the activities carried out, mostly children who become the promoters of reading in their families in the localityof USME.The participants are initially apprentices of the Administrative Management Center - CGA, who belong to theTechnologist in Library Management program, responsible for applying the knowledge acquired in the trainingprocesses towards social - community work. As a result, levels of social and cultural impact were evidenced byproviding the library and its users with material processed and administered according to the internationalpolicies available for its management, through the KOHA information system.